2009
DOI: 10.4269/ajtmh.2009.80.379
|View full text |Cite
|
Sign up to set email alerts
|

Urine Antigen Detection for the Diagnosis of Human Neurocysticercosis

Abstract: Neurocysticercosis (NCC) is a major cause of seizures and epilepsy. Diagnosis is based on brain imaging, supported by immunodiagnosis in serum or cerebrospinal fluid (CSF). Lumbar puncture is invasive and painful. Blood sampling is slightly painful and poorly accepted. Urine antigen detection has been used for other parasites and tried in NCC with suboptimal performance. We used a monoclonal antibody-based ELISA to detect Taenia solium antigens in urine from 87 Peruvian neurocysticercosis patients (viable cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 31 publications
0
22
0
2
Order By: Relevance
“…Extraparenchymal NCC, on the other hand, presents very high antigen levels, which have already been shown to reflect the evolution of the disease. 14,15,27,41 Antigen detection by a monoclonal antibody-based ELISA is a reliable tool to evaluate the response to antiparasitic treatment in the porcine model and may prove useful to monitor the efficacy of antiparasitic treatment in human NCC, guiding medical decisions along patient follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraparenchymal NCC, on the other hand, presents very high antigen levels, which have already been shown to reflect the evolution of the disease. 14,15,27,41 Antigen detection by a monoclonal antibody-based ELISA is a reliable tool to evaluate the response to antiparasitic treatment in the porcine model and may prove useful to monitor the efficacy of antiparasitic treatment in human NCC, guiding medical decisions along patient follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Antigen-ELISA has been widely used to detect cysticercosis in humans as well as in pigs. 14,15,[24][25][26][27] Using serial posttreatment serum circulating antigen levels in pigs, we assessed whether the changes in circulating antigen levels correlate with the response to antiparasitic treatment, and whether antigen levels at the time of necropsy correlate with the final infection burden.…”
Section: 19mentioning
confidence: 99%
“…162 We have found 92% sensitivity in patients with two or more viable cysts, and 62.5% in single lesion cases using the MoAbs described by Van Kerckhoven et al, 136 as well as a strong correlation between serum and urine levels of antigen. 163 Mwape et al 164 tested paired urine and serum samples collected in Zambia and Ecuador. A very high agreement (90%) was found between samples of the same individual, but lower specificity when urine samples were tested.…”
mentioning
confidence: 99%
“…The system has been used for cattle and porcine diagnosis, seroepidemiological surveys in endemic regions, and NCC detection and differentiation between active and inactive NCC (Dorny et al 2003;Nguekam et al 2003;Mwape et al 2013). Recently, these authors have confirmed the utility of urine samples for cysticercosis diagnosis (Castillo et al 2009;Mwape et al 2011).…”
Section: Immunodiagnosismentioning
confidence: 70%